Older adults with chronic diseases: perception of quality of life, resilience and social support in pandemic - Marín Cipriano, Caroline Gabriela (2024)
Objective: to establish the correlation between the perception of quality of life, resilience and social support in older adults who suffer from a chronic disease of Cercado de Lima. Materials and methods: it had a non-experimental-cross-sectional design and correlational type of study. A census was carried out in a population of 57 older adults of both sexes, with a diagnosis of a chronic disease. Pearson and Spearman statistical tests were mainly used. Results: significant correlations were found between quality of life and resilience (Rho=0.28); the dimension of resilience (acceptance of self and life) was also associated with social support (Rho=0.26) and with sociodemographic factors such as male sex, time of diagnosis and not having a caregiver. Also, resilience with married or cohabiting marital status and not forgetting to take medication; In addition, social support and the number of children were associated. Conclusion: older adults who perceive an adequate quality of life, despite suffering from a chronic illness, show an adequate capacity for resilience and perceive social support from their environment, which facilitates coping with adverse situations.